Effect of Service Quality on Perceived Value, Satisfaction and Loyalty of Customers: A Study on Selected Hospitals of Chhattisgarh - Dubey, Pushkar; Sahu, Satish Kumar (International Journal of Computer Sciences and Engineering, 2025)
The aim of the study was to predict the effect of service quality on perceived value, customer satisfaction and customer loyalty in hospitals of Chhattisgarh. A 22 item scale (under five dimensions namely tangibility, reliability, responsiveness, assurance, empathy) of service performance developed by Cronin and Taylor, 1994 was used to access the service quality of hospitals under study. Self-structured questionnaire was administered for measuring the perceived value, customer satisfaction and customer loyalty of hospitals under study. Data collection was made with the help of 120 respondents having fulfilled the inclusion criteria of research. Five different hospitals were chosen for the purpose of the study. Purposive sampling technique for data collection. The hypothetical model was evaluated by the help of structural equation modelling and the result was a good model fit. The result concludes that service quality has positive and direct effect on customers perceived value, customer’s satisfaction and customer loyalty in hospitals of Chhattisgarh